The acts and ordinances of the Governor and Council of New South Wales. - New South Wales; Brisbane, Thomas, Sir, 1773-1860.; Darling, Ralph, Sir, 1775-1858.; Bourke, Richard, Sir, 1777-1855.; Great Britain. Parliament; New South Wales. Governor; New South Wales. Legislative Council (Sydney : Printed by E. H. Statham, 1838)
Acts and ordinances passed during the administrations of Brisbane, Darling, Bourke.
v.1. 1824-1831 -- v.2, pt.1. 1832-1837 --v.2, pt.2. 1832-1837.
Includes indexes.
Ferguson, J.A. Bibliography of Australia
Keywords: Law -- New South Wales; New South Wales -- Politics and government -- 1788-1851.